The Mortality Peer Review Panel: a report on the deaths on operations of UK Service personnel 2002–2013. Issue 2 (25th February 2014) - Russell, Robert; Hunt, N; Delaney, R
Abstract : Introduction: Review of adverse outcomes is an essential element of healthcare governance. For each operational death, the post-mortem is attended by a member of Academic Department of Military Emergency Medicine and the case is assessed by a Mortality Peer Review Panel comprised of Defence Professors and other clinical and technical experts. Methods: A search was conducted of the Joint Theatre Trauma Registry (JTTR) for all UK military death reviews held from January 2002 to November 2013 and the judgement made by the Mortality Peer Review panel. Cases are awarded a 'salvageability' rating between S1 (salvageable) and S4 (not salvageable). Cases graded S1–3 are then assessed further for tactical, clinical or equipment factors that affected the outcome. Results: There were 621 deaths recorded on the JTTR and 517 (83.3%) were due to hostile action. The Killed in Action to Died of Wounds ratio is 6.28 : 1. Explosive mechanisms of injury were responsible for 55.65% of combat deaths and penetrating mechanisms 28.71%. An average of 10.56 injuries was recorded per casualty and the mean number of body regions affected was 3.34. The Peer Review Panel decided that 91.1% cases were not salvageable (S4); this figure is 93.5% if the deaths due to hostile action are considered separately. Conclusions: The severity of modern military trauma is overwhelming in nature and, along with trauma scoring systems, clinical peer review is an essential part of healthcare governance. The process also helps inform and direct research within clinical and force protection fields.